Effects of Climate Change Adaptation on Agricultural Productivity in Malakand (Khyber Pakhtunkhwa) (Journal of Asian Development Studies, 2024)
The study was conducted to investigate the effects of climate change adaptation on agricultural productivity in selected villages of District Malakand, Khyber Pakhtunkhwa, Pakistan. Adapting to climate change in District Malakand, is vital for helping farmers protect their crops from unpredictable weather, ensuring they can continue to grow enough food. Data were collected from 143 sampled households from Kot, Maina, and Mungai through a semi-structured questionnaire, and to analyze the data, descriptive statistics and binary logit regression were used. The study identified various adaptation strategies used by farmers for climate change and the effects of these adaptations on agriculture productivity. The adaptation strategies include changes in irrigation practices, adjustment of sowing periods, and the use of chemical fertilizers etc. Binary logit regression result indicates that the co-efficient and significance of the sample respondents for age (β=.058, p=.024), education (β=.111, p=.025), family size (β=.234, p=.007), income (β=.000, p=.018), landholding (β=.224, p=.036), farming experience (β=.090, p=.031), and tenancy status (β=1.120, p=.045) had a positive and significant relationship with adapting climate change adaptation strategies for agriculture productivity while the specific strategies for climate change adaptation is (β=-1.385, p=.023) had a negative and significant relationship with adapting climate change effect for agriculture productivity. The study recommended the formulation of a comprehensive national climate action plan, increased investment in rural infrastructure, and targeted policy measures to support the agricultural sector.